A proposal for individualized administration of energy and protein in the critically ill with obesity - K. Georg Kreymann; Geraldine de Heer; Arved Weimann (Nutrition in Clinical Practice, 2026)
Abstract The increasing prevalence of obesity has transformed intensive care and nutritional therapy of patients with obesity from a specialized problem to standard care. The dilemma in providing nutrition to critically ill patients with obesity is that current and historical nutritional guideline recommendations are based on expert opinion, are divergent, and are sometimes contradictory. None has been evaluated in a clinical trial. All but one are based on body weight, which results in a sex difference in the protein dose per fat free mass (FFM). We propose a standardized body weight (SBW 22 ) to determine energy delivery, but to measure FFM as the reference parameter for protein administration. In case FFM cannot be measured, we describe an estimation based on measurements of 1420 healthy humans. While energy delivery based on SBW 22 will result in a progressive hypoalimentation (based on calories/kg body weight) with increasing body mass index (BMI), a protein dose based on FFM will ensure an equal protein delivery over a broad range of BMI for both sexes. We propose this simple and physiological approach that should be evaluated in a clinical trial.